PENGENALAN TEKNOLOGI DIGITAL BERBASIS INTERNET OF THINGS (IoT) DI SMA NEGERI 1 KABUPATEN TANGERANG - Suhendi, Agus; Hamuda, Hayadi; Susilistia Agustini, Eneng (Tensile : Jurnal Pengabdian Kepada Masyarakat, 2024)
Abstract: In the field of education, the Internet of Things is a solution and supports a learning process that is tailored to the needs of each student, increasing competence, while linking virtual and physical classrooms to make learning more comfortable, accessible from anywhere and at any time. Apart from that, IoT also provides more efficient work for teachers and students, in community service activities (PkM) an introduction to the use of the internet of things (IoT) has been carried out for students of SMA Negeri 1 Tangerang Regency. The introduction of IoT to students is intended to be able to understand new technological developments in the fields of computer science and digital communication technology. Internet of things (IoT) is a concept that aims to expand the benefits of continuously connected internet connectivity and can be used in education, health, buildings, companies, homes, offices and industry to control electronic equipment such as room lights, turning off the air conditioner, turn off the tv remotely which can be operated via a computer network. By applying IoT to an object, someone can find out information related to that object directly from a distance as long as it is connected to the internet. This technological development needs to be conveyed to school students considering its important role in the monitoring and control system of an object remotely just by using the Blynk application on a smartphone. As a result of this PkM activity, students were very enthusiastic about listening and interested in trying the Internet of Things (IoT). Keywords: Internet of Things (IoT), Learning Media, Blynk Application on Smartphone